2016
DOI: 10.1111/lsq.12147
|View full text |Cite
|
Sign up to set email alerts
|

Public Expectations of State Legislators

Abstract: When members of Congress neglect the needs of their districts or vote contrary to the wishes of their constituents, their public approval suffers. Does the same hold true for representatives at the state level? Using experiments, I explore whether people dole out similar rewards and penalties to state legislators and members of Congress for their successes and shortfalls in representing constituents. I find that a similar model of political accountability travels from national politics to state politics. Peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Reelection-seeking parliamentarians are indeed expected to act in view of maximizing their support in subsequent elections (Mayhew, 1974), while voters are expected to take the incumbents' performance into account when casting their vote (Ferejohn, 1986). There have been numerous publications documenting the impact of constituency-oriented activities on reelection (Norris, 1997;Wolak, 2017;Chiru, 2018). There is however less real-world evidence concerning the effectiveness of MPs' personal vote-seeking strategies through work inside the parliament (Papp and Russo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Reelection-seeking parliamentarians are indeed expected to act in view of maximizing their support in subsequent elections (Mayhew, 1974), while voters are expected to take the incumbents' performance into account when casting their vote (Ferejohn, 1986). There have been numerous publications documenting the impact of constituency-oriented activities on reelection (Norris, 1997;Wolak, 2017;Chiru, 2018). There is however less real-world evidence concerning the effectiveness of MPs' personal vote-seeking strategies through work inside the parliament (Papp and Russo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the constituents' side, some work has demonstrated that defective behavior toward the party can appeal to voters, as it is interpreted as a signal of integrity and trustworthiness of the representative (e.g., Campbell et al 2016;Carson et al 2010). Constituents have also occasionally been surveyed about whether they prefer representatives to follow the party line or other considerations (e.g., Carman 2006;Méndez-Lago and Martínez 2002;Wolak 2017).…”
Section: Personalizationmentioning
confidence: 99%
“…Research on the demand‐side of representation offers a useful starting point for answering this question, as it reveals how individuals weigh different styles of representation. These studies suggest that the public prefers legislators who respond to constituency preferences over those who focus on constituency services or the preferences of other actors (Bengtsson & Wass, 2011; Carman, 2007; Doherty, 2013; Griffin & Flavin, 2011; Harden, 2016; Lapinski et al, 2016; Wolak, 2017). However, this work cannot tell us whether, and under what circumstances, targeted representation is viewed more or less favorably than broader constituency representation, as it focuses exclusively on the latter.…”
Section: Constituency Heterogeneity and Targeted Representationmentioning
confidence: 99%